(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Sugarcane is among the main crops that compose Brazilian’s agribusiness. Therefore, cropping has a significant economic and social role, as production increases yearly. Currently, in Brazil, the mechanized harvest of sugarcane is growing fast in most of the country. The improvement in the harvester’s performance allows for fewer expenses and a higher operating yield. This study aimed to analyze the correlation between fuel consumption and maneuvering time of sugarcane harvesters in three different areas (W1 > 20 ha, 10 ha < W2< 20 ha, and W3 < 10 ha). Were calculated fuel consumption per maneuver in each area and analyzed how this value can change due to the tracks’ spatial variability combined with the machine’s hourly consumption. Based on the variable maneuvering time results and consumption per maneuver, the treatment W3 was the one that obtained the lowest fuel consumption with the T maneuver, due to the shorter mean maneuvering time, besides the more significant available track space to perform them. So that is the best configuration that aims at more significant savings in production cost.